Implications of Makharij al-Huruf Learning in Improving The Rote Cauldron of The Qur'an Learners - Jhonha Ilham Hasibuan (Program Pascasarjana UMSB, 2022)
The development of tahfiz institutions is currently experiencing a drastic increase in quantity, but not a few tahfiz learning organizers are still low in attention to the quality of Quran memorization. This research aims to reveal how the quality of memorization of the Qur'an through intense learning of makharij al-surat. Research is carried out with a qualitative approach of the type of case study, research data is collected through participatory observations, this technique is considered appropriate because the data collected and then analyzed in the form of cases that occur at the research site. The study findings are that makharij al-surat is taught intensely before the start of tahfiz learning, learning is done with talqin, talaqqi, playing audio visuals and tasmi'. Memorization of the Qur'an of learners who follow the learning of makharij al-surat megalami improvement of quality, every letter, word and verse of the Qur'an that has been memorized by students at the end of the observation there are no errors in the aspects of makharij al-surat and tajwid.